EARLY SHORTTERM DOXYCYCLINE THERAPY IN PATIENTS WITH ACUTE MYO- CARDIAL INFARCTION AND LEFT VENTRICULAR DYSFUNCTION TO PREVENT THE OMINOUS PROGRESSION TO ADVERSE REMODELING (Неотложная медицинская помощь)
Источник: Cerisano G., Buonamici P., Valenti R., et al. Early short-term doxycycline therapy in patients with acute myocardial infarction and left ventricular dysfunction to prevent the ominous progression to adverse remodelling: the TIPTOP trial // Eur Heart J. – 2014. Vol. 35, N. 3. – P. 184–191.